CD34 expression does not correlate with immunophenotypic stem cell or progenitor content in human cord blood products - Mantri, Sruthi (Blood Adv, 2020)
The CD34(+) compartment of human cord blood contains a range of HSPC immunophenotypes, among which the Lin(−)CD34(+)CD38(+)CD127(+) CLP is rare. There is no correlation between the frequencies of CD34(+) cells and immunophenotypic HSC in umbilical cord blood products.